2015
DOI: 10.3126/ijls.v9i3.12440
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Physical Victimization among Male and Female High School Students in Iran

Abstract: School bullying is a common, problematic behavior among children that can have long-term adverse consequences for the victims of bullying. School bullying may take many forms, such as physical, verbal, and relational or social. So the purpose of this study was to compare physical victimization among male and female high schools students of Boukan city in Iran in academic year 2013-14. Four schools were selected by random cluster sampling. Data collected using Iranian form of bullying victimization scale (B.V.S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Therefore the first hypothesis is accepted. These findings are supported by the research by Wani [4], Veiskarami et al [14], Akhtar & Kushwaha [15], Talukdar & Deka [16], Khatri [17], Bettencourt & Miller [18], and Malik & Katyal [19], It is also divulge there is significant mean difference between the self esteem scores of boys and girls, because obtained t-value (3.45) was found significant at 0.01 level. Mean, S.D, SEM, of boys and girls were found [boys, (M= 14.20, S.D= 2.48, SEM= 0.41), girls (M= 12.62, S.D=1.03, SEM=0.17)] Therefore the second hypothesis is also accepted.…”
Section: Discussionsupporting
confidence: 79%
“…Therefore the first hypothesis is accepted. These findings are supported by the research by Wani [4], Veiskarami et al [14], Akhtar & Kushwaha [15], Talukdar & Deka [16], Khatri [17], Bettencourt & Miller [18], and Malik & Katyal [19], It is also divulge there is significant mean difference between the self esteem scores of boys and girls, because obtained t-value (3.45) was found significant at 0.01 level. Mean, S.D, SEM, of boys and girls were found [boys, (M= 14.20, S.D= 2.48, SEM= 0.41), girls (M= 12.62, S.D=1.03, SEM=0.17)] Therefore the second hypothesis is also accepted.…”
Section: Discussionsupporting
confidence: 79%
“…Further, there is a big volume of studies which contrast with the current findings. For example Veiskarami et al (2015) found in their study that boys average score on aggression was higher than girls. Bettencourt and Miller (1996) also found out a contrast to the current study suggesting that the men who are unprovoked are more aggressive as compare to women.…”
Section: Ns: Not Significantmentioning
confidence: 91%
“…The results also showed that boys justified physical aggression more easily than girls. Veiskarami et al (2015) conducted a study among males and females who are victims of physical aggression. Four schools from Iran were selected for the study.…”
Section: Review Of Literaturementioning
confidence: 99%
“…In fact, despite examining the background texture in the general motivational process model of Skinner et al (17), fewer studies have examined the role of self-perceptual systems as a mediator between background texture and psychological consequences. For example, Veiskarami et al (29) stated that classroom management style is related to AWB through academic motivation, and Upadyaya and Salmela-Aro (30) reported that academic engagement can be mediate the relationship between classroom management and AWB. Although based on the above studies, it seems that variables such as academic motivation and engagement can play a mediating role in the relationship between school culture and AWB, in the meantime, some basic variables have been neglected, among which are basic psychological needs.…”
Section: Introductionmentioning
confidence: 99%